"I don't need people to tell me I'm pretty on social media:" A qualitative study of social media and body image in early adolescent girls. (December 2017) - Burnette, C. Blair; Kwitowski, Melissa A.; Mazzeo, Suzanne E.
Highlights: 7th–8th grade girls from a small single-sex school were interviewed in focus groups. Social media use was high and visual platforms Instagram and Snapchat most popular. Girls minimized the influence of social media on social comparison and body image. Girls displayed high media literacy, appreciation of diversity, and confidence. Attitudes were primarily shaped by parental support and positive school environment. Abstract: Social media appear to contribute to body dissatisfaction in adolescents, although few empirical studies exist. This study used six focus groups (total N  = 38) to explore relations between social media use and body image in early adolescent girls (ages 12–14). Thematic analysis identified patterns in the data. In this sample, social media use was high. Girls endorsed some appearance concerns and social comparison, particularly with peers. However, they displayed high media literacy, appreciation of differences, and confidence, strategies that appeared helpful in mitigating the potential negative association between social media exposure and body image. Girls reported these characteristics were nurtured by positive parental influence and a supportive school environment. Results support an ecological approach to the prevention of body dissatisfaction. Although peer influence strengthens throughout adolescence, current findings suggest that parents and the school environment are associated with girls' attitudes and behaviors regarding social media and body image.